2019
DOI: 10.1073/pnas.1902566116
|View full text |Cite
|
Sign up to set email alerts
|

Generation of hypoimmunogenic human pluripotent stem cells

Abstract: Polymorphic HLAs form the primary immune barrier to cell therapy. In addition, innate immune surveillance impacts cell engraftment, yet a strategy to control both, adaptive and innate immunity, is lacking. Here we employed multiplex genome editing to specifically ablate the expression of the highly polymorphic HLA-A/-B/-C and HLA class II in human pluripotent stem cells. Furthermore, to prevent innate immune rejection and further suppress adaptive immune responses, we expressed the immunomodulatory factors PD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
220
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(248 citation statements)
references
References 46 publications
3
220
0
4
Order By: Relevance
“…The ability to generate hiPSCs at an affordable cost and in a timely manner will be necessary to assure the success of future hiPSC-derived cell therapies. Moreover, it will be essential to demonstrate that hiPSC-based therapies, whether using autologous donors or through the development of universal cell lines, are safe [11; 12; 13]. Here, we provide evidences that hiPSCs are the target of NK cells in vitro and in humanized mice.…”
Section: Discussionmentioning
confidence: 90%
“…The ability to generate hiPSCs at an affordable cost and in a timely manner will be necessary to assure the success of future hiPSC-derived cell therapies. Moreover, it will be essential to demonstrate that hiPSC-based therapies, whether using autologous donors or through the development of universal cell lines, are safe [11; 12; 13]. Here, we provide evidences that hiPSCs are the target of NK cells in vitro and in humanized mice.…”
Section: Discussionmentioning
confidence: 90%
“…Second, increasingly complicated genome engineering approaches can be applied to iPSCs, followed by single clone expansion and thorough characterization to obtain a clonal and genetically homogenous population with minimal off-target risk. Third, the seed iPSC clone can be expanded in large scale, and when combined with the recently reported techniques in making immune-tolerant universal iPSCs [25][26][27] , CAR-iMac can be developed into an off-the-shelf product with unlimited sources. The last two points are particularly useful when the effector cells from primary cell sources are difficult to engineer and to expand which is the case for PBMC-derived macrophage cells.…”
Section: Discussionmentioning
confidence: 99%
“…We show here that the forced expression of eight immunomodulatory factors in cells is sufficient to escape immune rejection in allogeneic hosts. Other attempts to engineer allotolerated cells have focused on removing MHC genes and/or the introduction of just one or a few factors [2][3][4]32 . The emphasis on MHC genes is clearly justified since they are the primary source of allogenic antigens during transplantation and loss of these molecules is often coincident with immune evasion in nature 33 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that replacement of HLA class I in human PSCs with the inhibitory HLA-E prevented NK and CD8 T-cell responses in vitro as well clearance after engraftment into humanized mouse models 2 . Others have combined deletion of MHC class I and II with the forced expression of one or more immunosuppressive transgenes 3,4 . While promising, MHC-modified or null cells still express minor antigens and other gene polymorphisms that can become targets of rejection and humoral immunity over time [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%